Gene Expression Dynamics in Rice Peduncles at the Heading Stage - Kandpal, Manu; Vishwakarma, Chandrapal; Krishnan, Kushagra; Chinnusamy, Viswanathan; Pareek, Ashwani; Sharma, Manoj K.; Sharma, Rita (Frontiers in Genetics, 2020)
Improving grain yield in the staple food crop rice has been long sought goal of plant biotechnology. One of the traits with significant impact on rice breeding programs is peduncle elongation at the time of heading failing which leads to significant reduction in grain yield due to incomplete panicle exsertion. To decipher transcriptional dynamics and molecular players underlying peduncle elongation, we performed RNA sequencing analysis of elongating and non-elongating peduncles in two Indian cultivars, Swarna and Pokkali at the time of heading. Along with genes associated with cell division and cell wall biosynthesis, we observed significant enrichment of genes associated with auxins, gibberellins and brassinosteroid biosynthesis/signaling in the elongating peduncles before heading in both the genotypes. Similarly, genes associated with carbohydrate metabolism and mobilization, abiotic stress response along with cytokinin, abscisic acid, jasmonic acid and ethylene biosynthesis/signaling were enriched in non-elongating peduncles post heading. Significant enrichment of genes belonging to key transcription factor families highlight their specialized roles in peduncle elongation and grain filling before and after heading, respectively. A comparison with anther/pollen development-related genes provided 76 candidates with overlapping roles in anther/pollen development and peduncle elongation. Some of these are important for carbohydrate remobilization to the developing grains. These can be engineered to combat with incomplete panicle exsertion in male sterile lines and manipulate carbohydrate dynamics in grasses. Overall, this study provides baseline information about potential target genes for engineering peduncle elongation with implications on plant height, biomass composition and grain yields in rice.